Does Community Cohesion Present Challenges for Social Protection Programs? Case of the Program of Subsidized Rice for the Poor in Purbalingga District - Sutiyo, Sutiyo; Rahardjanto, Tri; Sinaga, Jona Bungaran Basuki; Harahap, Agus Supriyadi (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
This study aims to explore the potential linkage of cohesiveness with the problems of distribution inaccuracy of social protection programs in Indonesia. It will focus on the program of subsidized rice for the poor, with a case study in Purbalingga district. Through qualitative and descriptive statistic methods, this study presents the existence of conceptual and empirical linkage of cohesiveness with distribution inaccuracy. Community cohesiveness present challenges for the top-down nature of program design and implementation. Preserving cohesiveness has been the main justification of almost al actors in doing equal distribution of the program. Solution for this problem will depend on government willingness to initiate community based targeting system, involving community and local leaders in enlistment and distribution of the program through deliberation system.